STUDI KASUS PELAKSANAAN PELAYANAN PROVIDER INITIATED HIV TESTING AND COUNSELING PADA DONOR DARAH REAKTIF HIV DI UNIT TRANSFUSI DARAH PMI KOTA SURAKARTA - Isnaeni, Siti; Fridayanti, Warni (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2018)
The HIV epidemic is a serious problem as well as a serious challenge to the health of the world community. HIV transmission can be through blood transfusion, if the blood is already infected with HIV. The role of the Red Cross Blood Transfusion Unit in preventing HIV transmission through blood transfusions is by screening blood. The number of cases of blood-stained bags re-infected with HIV in Surakarta is quite high. However, HIV-reactive-trained donors are not aware of their HIV infection status. The Provider Initiated HIV Testing and Counseling approach needs to be provided by the Red Cross Blood Transfusion Unit so that these reactive donors can know their HIV status and get comprehensive treatment and can behave that are not at risk so as not to transmit HIV to others. The purpose of this research is to describe the implementation ofÂ  PITC in UTD PMI Surakarta. This reseach uses qualitative method with case study research design. Taking the subject of this research using purposive sampling technique. The primary informant in this study was a counselor at UTD PMI Surakarta. The triangulation informant consisted of one counselor at the VCT Hospital clinic and one donor who was reactive to HIV. Data were collected by in-depth interviews and observations. Data processing and data analysis is by way of data reduction, data display and verification. The results show that the UTD PMI Surakarta has been implementing PITC for HIV reactive blood donors since 2014. The PITC program succeeded in making HIV-reactive-trained donors accessible to HIV treatment services, behaving in a safe manner in order not to transmit HIV to others, and realizing that they can not donate their blood to anyone else. A very important factor in the implementation of PITC in UTD PMI Surakarta is because it has qualified and committed human resources, has good knowledge, and has strong motivation. In addition, UTD PMI Surakarta already has complete facilities and infrastructure including VCT clinic. Keywords: PITC, UTD PMI, HIV reactive blood donor, screening